2023
DOI: 10.1097/md.0000000000032804
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral Xiao-xian decoction combined with acupoint application therapy on pediatric adenoid hypertrophy: A randomized trial

Abstract: Background: This study aimed to observe the clinical effects of Xiao-xian decoction combined with acupoint application therapy (AAT) for treating pediatric adenoid hypertrophy (AH). Methods: We randomly divided 93 AH children into 3 groups: AAT alone; Xiao-xian decoction + AAT; control: Montelukast oral therapy. All participants were treated for a month. We used the traditional Chinese medicine syndrome score to evaluate the clinical efficacy and the obstructive sleep apnea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(36 reference statements)
0
0
0
Order By: Relevance
“…Similar to Zaho's reports, the case presented by Deng showed the effectiveness of sphenopalatine ganglion electroacupuncture in widening the patency of the nasopharyngeal space in a 9-yearold boy (79,81). While these are interesting reports, they do require further medical analysis.…”
Section: Acupuncturesupporting
confidence: 70%
See 1 more Smart Citation
“…Similar to Zaho's reports, the case presented by Deng showed the effectiveness of sphenopalatine ganglion electroacupuncture in widening the patency of the nasopharyngeal space in a 9-yearold boy (79,81). While these are interesting reports, they do require further medical analysis.…”
Section: Acupuncturesupporting
confidence: 70%
“…Some Chinese studies have indicated the efficacy of traditional Chinese herbal medicine for AH treatment in children, which showed better outcomes than Western medicine results (77-79). Zhao showed that oral Xiao-xian decoction combined with acupuncture (acupoint application) improved clinical symptoms of adenoid hypertrophy and may be suitable for long-term treatment (79).…”
Section: Anti-leukotriene Therapiesmentioning
confidence: 99%